Construction of the bicyclo[3,1.0]hexane template of a conformationally locked carbocyclic adenosine via an olefin keto-carbene cycloaddition - Shin, KJ; Moon, HR; George, C; Marquez, VE (AMER CHEMICAL SOC, 2000)
An intramolecular olefin keto-carbene cycloaddition reaction created the bicyclo[3.1.0]hexane template 10 that was necessary for the synthesis of carbocyclic amine 15. This amine is a direct precursor to a family of rigid nucleosides that are conformationally locked in the Southern hemisphere of the pseudorotational cycle. The synthesis of the conformationally locked adenosine analogue is reported herein as an illustrative example of the methodology. The racemic (South)methanocarba adenosine analogue (+/-)-4 is the first example of a conformationally locked ribonucleoside Version in the Southern hemisphere.
Keywords: REVERSE-TRANSCRIPTASE; BIOLOGICAL-ACTIVITY; NEPLANOCIN-C; SUGAR RING; NUCLEOSIDES; ANALOGS; THYMIDINE; OLIGONUCLEOTIDES; CRYSTAL